Modular Molecules: Site‐Selective Metal Substitution, Photoreduction, and Chirality in Polyoxometalate Hybrids. Issue 43 (9th September 2014) - Vonci, Michele; Akhlaghi Bagherjeri, Fateme; Hall, Peter D.; Gable, Robert W.; Zavras, Athanasios; O'Hair, Richard A. J.; Liu, Yuping; Zhang, Jie; Field, Matthew R.; Taylor, Matthew B.; Du Plessis, Johan; Bryant, Gary; et al.
Abstract The first members of a promising new family of hybrid amino acid–polyoxometalates have emerged from a search for modular functional molecules. Incorporation of glycine (Gly) or norleucine (Nle) ligands into an yttrium‐tungstoarsenate structural backbone, followed by crystallization with p‐methylbenzylammonium (p‐MeBzNH3+) cations, affords (p‐MeBzNH3)6K2(GlyH)[AsIII4(YIIIWVI3)WVI44YIII4O159(Gly)8‐ (H2O)14]⋅47 H2O (1) and enantiomorphs (p‐MeBzNH3)15(NleH)3 [AsIII4(MoV2MoVI2)WVI44YIII4O160(Nle)9(H2O)11][AsIII4(MoVI2WVI2)‐ WVI44YIII4O160(Nle)9(H2O)11] (generically designated 2: L‐Nle, 2 a; D‐Nle, 2 b). An intensive structural, spectroscopic, electrochemical, magnetochemical and theoretical investigation has allowed the elucidation of site‐selective metal substitution and photoreduction of the tetranuclear core of the hybrid polyanions. In the solid state, markedly different crystal packing is evident for the compounds, which indicates the role of noncovalent interactions involving the amino acid ligands. In solution, mass spectrometric and small‐angle X‐ray scattering studies confirm maintenance of the structure of the polyanions of 2, while circular dichroism demonstrates that the chirality is also maintained. The combination of all of these features in a single modular family emphasizes the potential of such hybrid polyoxometalates to provide nanoscale molecular materials with tunable properties.